Assesment of Corporate Social Responsibility Using Fuzzy Analytic Hierarchy Process - Staňková, Štěpánka; Zapletal, František (Univerzita Pardubice, 2016)
Together with the managerial decision to run a business in accordance with Corporate Social Responsibility (CSR) principles, important steps dealing with the necessity of systematic CSR evaluation and measurement should be discussed. Organizations could choose from varied evaluation tools and procedures such as a special CSR audit, a certification, a quality mark, a non-financial report, a standard, or sustainability indices that differ in methodologies, complexity and scopes of their appropriate usage in various business sectors and organization structures. The main goal of this paper is focused on the application of the linear goal programming priority method together with fuzzy analytic hierarchy process (in short LGPPM-FAHP) in a complex CSR assessment of three major telecommunication organizations operating in the Czech Republic (T-Mobile Czech Republic, a.s., Vodafone Czech Republic, a.s. and O2 Czech Republic, a.s.). This paper proposes a systematic approach to evaluate CSR using linguistic scales that enable a decision maker to express his/her uncertainty in decision-making processes. It is described how the LGPPM-FAHP could be used as a helpful managerial tool providing reliable sources for a CSR assessment.
Keywords: Business ethics; Corporate Social Responsibility; Fuzzy analytic hierarchy proces; Group decision making; Linear goal programming priority method; L14; M21